EVALUASI KESESUAIAN LAHAN KECAMATAN KARANGREJA KABUPATEN PURBALINGGA JAWA TENGAH SEBAGAI UPAYA PENINGKATAN PRODUKTIVITAS KOMODITAS SAYURAN - Anggraeni Nur Hidayah; Susilo Budiyanto; Endang Dwi Purbajanti (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Evaluation of land suitability was carried out in Karangreja sub-district to determine the land suitability class for vegetable commodities. This research was conducted to determine the limiting factors that resulted in a decrease in soil fertility in the local area. Land suitability classes were obtained in S2, S3, and N classes with limiting factors for water availability (wa), erosion hazard (eh), temperature (tc), root media (rc), and nutrient retention (nr). The limiting factor that’s spread evenly throughout the test area is the erosion hazard caused by the slope of the study area is classified as low to high. Improvement efforts as an agricultural area development that can be done are making drainage channels to improve the drainage system, making water absorption holes to reduce excess water on the land, making bench terraces to reduce slopes, and giving fertilizers in the form of zeolite or biochar to increase the level of soil cation exchange capacity.